(untitled) (Herald of the National Children’s Medical Center, 2025)
This study aimed to identify prognostic factors influencing survival outcomes in pediatric oncology patients treated at a tertiary-level hospital in Tashkent, Uzbekistan. A retrospective cohort of 108 children diagnosed with kidney tumors was analyzed using Cox proportional hazards regression. Eight cases (7.4%) were excluded due to missing data, leaving 100 patients for analysis. The cohort included 49 males (45%) and 59 females (55%), with a median age of 2.07 years (IQR: 0.95–4.01). Tumor characteristics were predominantly primary tumors in 88 patients (88%), while progressive tumors were observed in 10 patients (10%) and non-primary tumors in 4 patients (4%). Local growth into neighboring organs was detected in 40 cases (40%), and metastasis to distant organs was observed in 28 cases (28%). Histological analysis revealed nephroblastoma (Wilms tumor) as the most common diagnosis, accounting for 95 cases (95%), followed by mesoblastic nephroma in 3 cases (3%) and adenocarcinoma in 1 case (%). Data on histology were unavailable for 1 case (1%).